The Enlightenment of Bees - Linden, Rachel (Thorndike, Maine Center Point Large Print, 2019)
"Rachel Lindens contemporary womens fiction story speaks to the universal struggle of what it means to live a meaningful life where the passions we have meet the needs of the world. From the slums of Mumbai to a Hungarian border camp during the refugee crisis, Mia experiences the euphoria, disillusionment, and heartbreaking reality of humanitarian work abroad"--
Keywords: Women -- Fiction; Life change events -- Fiction; Humanitarian assistance; Fiction; Large type books; Romance fiction